Simple Priorities and Core Stability in Hedonic Games - Dinko Dimitrov; Peter Borm; Ruud Hendrickx; Shao Chin Sung (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper we study hedonic games where each player views every other player either as a friend or as an enemy. Two simple priority criteria for comparison of coalitions are suggested, and the corresponding preference restrictions based on appreciation of friends and aversion to enemies are considered. It turns out that the first domain restriction guarantees non-emptiness of the strong core and the second domain restriction ensures non-emptiness of the weak core of the corresponding hedonic games. Moreover, an element of the strong core under friends appreciation can be found in polynomial time, while finding an element of the weak core under enemies aversion is NP-hard. We examine also the relationship between our domain restrictions and some sufficient conditions for non-emptiness of the core already known in the literature.
Keywords: C71; A14; D20; 330; Additive separability; Coalition formation; Core stability; Hedonic games; NP-completeness; Priority; Spieltheorie; Koalition